Reforming Higher Education In Albania: The Scientific Research - Laze, Juljana (Mediterranean Journal of Social Sciences, 2011)
In the current development and perspectives in the Albanian education, reforms on the high education, bears the internaltendency for development, aiming on the integration of the Albanian society in the European regional development. This paper has on itsfocus the analysis of functioning and malfunctioning of the scientific research in Albania, which would highlight some of the problems itfaces, such as: a) Low research level; b) Unclear financing strategies and c) Deep separation between research and university as wellbetween research conclusion and market. System reformation of scientific research and technological development will lead to a rationalframe in which the actors would feel estimated and the society itself would experience the investment. In terms of an opened market theprocess of research integration in universities is unavoidable defined from the adjustment of university offers and labor market demands.